Novel biocompatible PBS-based random copolymers containing PEG-like sequences for biomedical applications: From drug delivery to tissue engineering. (July 2018) - Fabbri, Martina; Guidotti, Giulia; Soccio, Michelina; Lotti, Nadia; Govoni, Marco; Giordano, Emanuele; Gazzano, Massimo; Gamberini, Rita; Rimini, Bianca; Munari, Andrea
Abstract: A series of random poly(butylene succinate)-based copolymers, (poly(butylene/triethylene succinate) (P(BSmTESn)), containing ether-oxygen atoms were successfully synthesized by melt polycondensation of succinic acid and 1, 4-butanediol in the presence of triethylene glycol (TEG) (TEG content up to 40 mol%). The copolymers were characterized from the molecular, thermal, structural and mechanical point of view. Hydrolytic degradation studies were performed under physiological conditions. The biocompatibility of the samples under investigation through indirect and direct biocompatibility studies was investigated by using embryonic rat cardiac H9c2 cells. To evaluate the potential of these polymers also for controlled drug delivery systems, the diffusion profile of Dexamethasone, an anti-inflammatory drug, through nanoparticles prepared by oil-in-water miniemulsion process was investigated. Results showed that solid-state properties could be tailored nicely by simply varying copolymer composition. Crystallinity degree and hydrophobicity significantly decreased with the increase of triethylene succinate co-unit (TES) mol%. Moreover, hydrolytic degradation of PBS, depending on polymer crystallinity degree and hydrophilicity, was remarkably improved: the copolymer containing 40 mol% of triethylene succinate co-unit after 200 days lost over 22% of its initial weight. The newly developed biomaterials showed lack of cell cytotoxicity. Among them, PBS and the copolymers containing up to 20 mol% of TES co-units sustained a better cell adhesion and proliferation. In addition, such copolymers induced muscle phenotype commitment in H9c2 cells cultured onboard. Lastly, the release profile of Dexamethasone obeyed to a first order kinetic law, the copolymer richest in TES co-unit content showing the highest encapsulation capability and the fastest drug release kinetics. Anyway, PBS and the copolymers containing up to 20 mol% of TES co-unis sustained a better cell adhesion and proliferation, with the copolymers characterized by a myosin heavy chain expression, which appeared to be up to twofold increased on respect to the one of PBS homopolymer. Highlights: Novel biocompatible PBS-based copolymers for biomedical applications were successfully synthesized by solvent-free process. Mechanical properties are controllable and tunable from rigid plastics to soft elastomers. Copolymerization did not cause a worsening of PBS biocompatibility. Copolymerization improves the biodegradation rate under physiological conditions. Anti-inflammatory drug containing nanoparticles with different drug release rate have been obtained by miniemulsion.